Mammary gland tumours in the dog, a spontaneous tumour model of comparative value to human breast cancer - Sahabi, Kabiru; Rajendren, Sujey Kumar; Foong, Jia Ning; Selvarajah, Gayathri Thevi (Universiti Putra Malaysia Press, 2018)
Mammary gland tumours are the most common neoplasia diagnosed in the female dog. These tumours occur spontaneously or naturally as in humans, 50% of which are commonly diagnosed as malignant. Metastasis to other tissues especially the lung is a common cause of death in these dogs. Treatment of canine mammary gland tumours (CMT) involves mainly surgical resection with wide margin followed by chemotherapy with cytotoxic drugs for those with lymph node and distant metastasis. With the dog continuously described as a very suitable and valuable large animal model of human breast cancer, it becomes very obvious that CMT can be a model to further understand the biology of cancer as well as screening for new therapeutic agents that could be used to treat human breast cancer and CMT more effectively. This review focuses on research work that has been done on CMT over the past years, describing the epidemiology, diagnostics and recent advances in therapy for CMT as well as discussing the significance of the dog CMT as spontaneous animal model for human breast cancer.